Identification of a bisegmented double-stranded RNA virus (picobirnavirus) in calf faeces - Buzinaro, M. G.; Freitas, PPS; Kisiellius, J. J.; Ueda, M.; Jerez, J. A. (Bailliere Tindall, 2003)
To determine the incidence of rotavirus infection among dairy herds in the State of Sdo Paulo, Brazil, 576 faecal samples obtained from calves aged 1-45 days with and without diarrhoea, reared on 63 dairy cattle farms, were analyzed. Polyacrylamide gel electrophoresis (PAGE) identified 28 samples positive for group A rotavirus, while four samples, two diarrhoeic and two non-diarrhoeic, showed a bisegmented genome with a typical picobirnavirus pattern. Electron microscopy revealed spherical virus particles with a diameter of 37 nm and without a defined surface structure. The present study is the first report of a bisegmented virus identified in cattle in Brazil. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: picobirnavirus; diarrhoea; Cattle; PAGE